An application of bibliographic coupling of authors to the metric studies of information in Brazil: Scopus base (2014-2018) - Nogueira, Eurides Costa Tavares [UNESP]; Oliveira, Ely Francina Tannuri de [UNESP] (Univ Federal Rio Grande Sul, Fac Biblioteconomia & Comunicacao, 2023)
The relational analyzes of citations aim to map the thematic, theoretical and/or methodological similarities between articles, related to different variables: authors, documents, journals, countries or other units of analysis. There are two main methods of relational citation analysis: author bibliographic coupling analysis and author co-citation analysis, which, despite some similarities, present important differences and complement each other. This study aims to discuss theoretical, conceptual and applied aspects, inherent to the analysis of the author's bibliographic coupling, aiming to contribute to the reflections and development of theoretical-methodological studies and applied in the theme metric studies of information in Brazil, in the period from 2014 to 2018. More specifically, it aims to: know the proximity and proximity between researchers and their productions, in the articles typology, through the bibliographic coupling of authors; analyze the different looks and methodologies explained by the coupling, which define the identity of the citing authors, evaluating the proximity between them. The Scopus database was used, with a corpus of 731 articles produced in the period under analysis, on which the bibliographic coupling of authors was carried out. As a result, there was a predominance of researchers in the area of health, information science, engineering, management, and others with lesser prevalence. The bibliographic coupling network of authors with 36 most productive components and their respective connections was analyzed, with the strongest being the connections with the highest intensity of coupling between the two authors, through the citations in common between them. It was concluded that highly cited authors were found, but who were not coupled with prolific and well-known authors.
Keywords: coupling of bibliographic reference; bibliographic coupling of authors; information metric studies; citation analysis